PERTUMBUHAN DAN HASIL TIGA VARIETAS UBI JALAR (Ipomoea batatas L.) PADA TINGGI PETAKAN YANG BERBEDA - Adrianus Adrianus (AGRICOLA, 2012)
This study aim of the research is to find  the  growth and production of three varieties of sweet potato in different heights of maps. The resulted conducted in the experimental farm of Faculty of Agriculture,  Hasanuddin University in Makassar from March to July 2011.  The experiment was prepared using the design plots split consisted of 15 cm high, 30 cm and 45 cm high and three varieties of sweet potato as a sub plot, consisting of Japanese variety, Power variety and Purple/Poiret variety.  The results of the research reveal that  Japanese variety produces an average of the highest number of leaves (125.78 strands), the largest number of branches (6.19 strands), the heaviest leaves (164.00 g),  the highest weight of tubers per hectare (19.96 tons / ha ) and highest weight per tuber (171.73 g) The Power of varieties produced on average the heaviest stalk (295.75 g), the heaviest weight of tuber per plant (539.35 g), the heaviest   economical tuber weight per plant  (473.03 g), heaviest biomass (969.44 g), the longest shoots (451.18 cm) and the highest number of tubers (4.77 pieces). The plot with 30 cm high (p2) produces an average heaviest leaves (146.70 g), while the plot 45 cm (p3),  product  an average  longest tubers (14.57 cm).